2010
DOI: 10.1097/qai.0b013e3181c7df8b
|View full text |Cite
|
Sign up to set email alerts
|

The Situation of Children Affected by HIV/AIDS in Southwest China: Schooling, Physical Health, and Interpersonal Relationships

Abstract: Objective To investigate the schooling, physical health and interpersonal relationships of children affected by HIV/AIDS in rural areas of southwest China. Methods Using a structured survey, quantitative data were collected on a total of 116 children and 114 of their caregivers. Results Parental illness or death adversely affected children’s school attendance as well as school performance. Over one-third (36.2%) of children reported being ill for more than 3 days during the previous 6 months; more orphans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Kinship and family networks become even more important during sickness (Xu et al, 2010;Kyaddondo et al, 2013). This study concurred in that most of the children lived with relatives.…”
Section: The Kinship Obligation and Idealsupporting
confidence: 80%
“…Kinship and family networks become even more important during sickness (Xu et al, 2010;Kyaddondo et al, 2013). This study concurred in that most of the children lived with relatives.…”
Section: The Kinship Obligation and Idealsupporting
confidence: 80%
“…Other stressors more common for AO were care giver mental health problems [40,41], less communication with caregivers [42], children engaging in excessive housework [31,38,43], and sibling separation [34,44]. Two studies reported AO were more likely to experience household relocation [31,34], while two others reported no differences based on orphan status [36,45].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the HIV epidemic, grandparents are a major source of childcare in most African countries (Mathambo & Gibbs, 2009), which leaves most households missing the middle generation (Karimli, Ssewamala, & Ismayilova, 2012). As grandparents have lost their support mechanisms in the form of their own children, this circumstance makes their grandchildren more vulnerable because these children may also have to assist with daily housework and farm chores (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Children who are heads of households need to work to obtain living necessities and, as a result, they might miss school (de Wagt & Connolly, 2005). Several studies has further indicated that significant predictors of school outcomes included household wealth (Smiley et al, 2010;Xu, Wu, Duan, Han, & Rou, 2010), living arrangements (Smiley et al, 2010;Steinberg et al, 2002;Yanagisawa, Poudel, & Jimba, 2010), and household structure (Nyamukapa & Gregson, 2005).…”
Section: Introductionmentioning
confidence: 96%